2001
DOI: 10.1054/bjoc.2001.2101
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of BAX is associated with poor prognosis in patients with epithelial ovarian cancer: a multifactorial analysis of TP53, p21, BAX and BCL-2

Abstract: Summary Traditional clinicopathological features do not predict which patients will develop chemotherapy resistance. The TP53 gene is frequently altered in ovarian cancer but its prognostic implications are controversial. Little is known on the impact of TP53-downstream genes on prognosis. Using molecular and immunohistochemical analyses we examined TP53 and its downstream genes p21, BAX and BCL-2 in ovarian tumour tissues and have evaluated the results in relation to clinico-pathological parameters, clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
70
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 41 publications
(36 reference statements)
9
70
1
1
Order By: Relevance
“…In our study, the mucinous, clearcell and endometrial carcinomas tended to have higher Bax expression level, whereas the serous, mucinous, mixed and clear-cell subtypes had a tendency to have lower Bcl-2 expression level. As was shown in several previous studies, Bcl-2 and Bax expression was not associated with histologic type and grade in our study [20,21].…”
Section: Discussionsupporting
confidence: 88%
“…In our study, the mucinous, clearcell and endometrial carcinomas tended to have higher Bax expression level, whereas the serous, mucinous, mixed and clear-cell subtypes had a tendency to have lower Bcl-2 expression level. As was shown in several previous studies, Bcl-2 and Bax expression was not associated with histologic type and grade in our study [20,21].…”
Section: Discussionsupporting
confidence: 88%
“…In subgroups related to the TP53 status, BCL-2 and BAX demonstrated an influence on CR or DFS, which was not seen in all tumours. Among other studies evaluating predictive significance of BCL-2 (Herod et al, 1996;Mano et al, 1999;Schuyer et al, 2001), including two published by Baekelandt et al (1999Baekelandt et al ( , 2000 on a comparable number of ovarian carcinomas, only Mano et al (1999) noticed higher frequency of CR in patients with BCL-2 negative tumours.…”
Section: Discussionmentioning
confidence: 91%
“…In regard to BAX expression, a few studies have addressed the issue of its clinical significance in advanced stage ovarian carcinomas; however, associations with CR or DFS have not been observed (Marx et al, 1997;Baekelandt et al, 2000;Sengupta et al, 2000;Schuyer et al, 2001). Recently, Schuyer et al (2001) found an association of BAX expression with progression-free survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations